Nature's Remedy for War's Scars: Leveraging Siddha Wellness Tourism and Blue Economy for Post-Conflict Ecological and Economical Recovery in Northern Sri Lanka - Gumuthagini, V.; Sharsaayini, T.; Sathiyaseelan, V. (Federation of Global Tamils, 2025)
This study examines how Siddha Medicine enables sustainable post-war recovery in Northern Sri Lanka. Using mixed methods (15 practitioner surveys, spatial analysis, pilot projects), it highlights Siddha's cultural revival (89% identify with Tamil heritage) and restoration of health (healing trauma and chronic disease). Marine-based therapies - seaweed (Padina gymnospora), pearl products (Pinctada fucata), saline springs - are Blue Economy compliant with the potential to create 500+ jobs, 78% for women. Challenges include fragmented policy, infrastructure absence (83% of sites), and resource depletion (32% species). Proposed solutions are block chain traceability, telemedicine, wellness trails, and Medicinal Marine Protected Areas, ensuring culture- based yet sustainable development.
Keywords: Marine conservation; Post-conflict recovery; Siddha Medicine; Sri Lanka; Sustainable tourism